Assessing Arabic Learning through a Game-Based Evaluation Tool for Year One Primary School Students - Aini, Nur; Listiani, Heni (Upgrade : Jurnal Pendidikan Teknologi Informasi, 2025)
An effective Arabic assessment model for first-grade students combines both formative and summative methods to evaluate foundational language abilities—like recognizing letters, understanding vocabulary, and forming basic sentences—as well as early analytical skills, such as identifying word roots and grasping simple grammar. These evaluations integrate engaging interactive tools, including digital quizzes, multimedia prompts, and educational games that adapt to each child’s learning pace while offering immediate feedback. This study aims to evaluate the effectiveness and accuracy of a game-based evaluation tool (Wordwall) in Arabic language learning for Year One primary students at MIN 2 Sumenep. This study used mixed method with a quasi-experimental design through pre-test and post-test of a study group. There were 28 students who completed ten interactive tasks, matching picture test, audiovisual quizzes, spin wheel activities, and letter sequencing exercises for fruit vocabulary. The result of this study showed that 78.6%-92.9% of students found Wordwall’s visuals, functionality, and motivational features engaging and easy to use. Overall, Wordwall delivered an 83% improvement in learning efficiency and achieved a 94,6% accuracy rate in vocabulary mastery. These findings concludes that game-based assessments can simultaneously boost engagement and assessment precision. The study’s novelty lies in focusing on early grade Arabic evaluation within the Merdeka Curriculum framework. Implications include recommending wider adoption of game based evaluation tools, structured teacher training in interactive design,